The Problem of Evil: Evaluating its Theological and Philosophical Implications for the Attributes of the “Good God” - OMOMIA, Austin; IFABIYI, Alaba Bukola (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
The problem of evil remains a profound challenge in theology and philosophy, particularly concerning the coherence of the attributes of a “Good God” in a world marred by suffering, injustice and moral evil. The purpose of this study is to critically evaluate the theological and philosophical implications of evil on the traditional attributes of God: goodness, omniscience and omnipotence. Employing a multidisciplinary approach, the study engages classical theodicies such as the Augustinian and Irenaean models, alongside philosophical arguments including the free will defense and process theology. Textual analysis and comparative evaluation of historical and contemporary sources guide the methodology. The findings reveal that while atheistic perspectives often present evil as incompatible with divine goodness, many theistic responses offer reasoned frameworks that preserve belief in a benevolent God. The study also uncovers existential dilemmas faced by individuals, particularly in reconciling faith with persistent natural and moral evils. The analysis shows that evil does not conclusively negate God’s goodness but rather invites deeper theological reflection and ethical responsibility. Conclusively, the research affirms that a nuanced understanding of divine attributes, in light of suffering, can sustain faith and inspire moral resilience. The contribution to knowledge lies in bridging classical theodicies with contemporary existential concerns, offering insights that support both academic discourse and lived religious experience.